Silica gel supported nickel-vanadium bimetallic catalyst as well as preparation method and application thereof
By using silica gel-supported nickel-vana bimetallic catalyst, the problem of taking into account both the catalyst activity and molecular weight distribution in the prior art was solved, and efficient production of polyethylene products was achieved, with good industrial application prospects.
Patent Information
- Application Number
- CN202411842515.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Existing polyethylene catalysts are difficult to take into account the width and catalytic activity of the product's molecular weight distribution, resulting in high production costs and poor product stability.
Silicone-supported nickel-vana bimetallic catalyst is used, which improves catalytic activity and expands the molecular weight distribution width of polyethylene products through the combination of silica gel, vanadium and nickel metal complexes.
It has achieved the improvement of the molecular weight distribution width and catalytic activity of polyethylene products while maintaining low production costs, and has good industrial prospects.
Smart Images

Figure CN119490544A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer catalysts, and in particular to a silica gel-supported nickel-vanadium bimetallic catalyst and a preparation method and application thereof. Background Art
[0002] Bimodal / broad distribution polyethylene has two peaks in its molecular weight distribution curve and a wide distribution range. Through the coordination between the high molecular weight component and the low molecular weight component, the bimodal / broad distribution polyethylene can have both excellent mechanical properties and good processing properties.
[0003] At present, there are three main processes for industrial production of bimodal / broad distribution polyethylene:
[0004] (1) Parallel reactor process, in which polymers with different molecular weight distributions are produced in two reactors and blended in a molten state; (2) Series reactor process, in which the catalyst is used to prepare polymers with different molecular weights in different reactors by changing the polymerization conditions; (3) Single reactor process, using catalysts with multiple active sites, single catalysts with multiple carriers, and mixed catalysts.
[0005] The production costs of the series reactor process and the parallel reactor process are both high, and the product stability is poor. The single reactor process has low production costs and good product stability, but the performance of the polyethylene product prepared is inseparable from the catalyst; the types of polyethylene catalysts that have been disclosed so far mainly include Ziegler-Natta catalysts, chromium catalysts and metallocene catalysts, etc., but the above-mentioned types of catalysts that have been disclosed have the problem of not being able to take into account both the product molecular weight distribution and catalytic activity when applied to polyethylene production. Specifically, the catalysts suitable for producing polyethylene with a wide molecular weight distribution have a relatively low catalytic activity; while the catalysts with high catalytic activity produce products with a relatively narrow molecular weight distribution, which are not suitable for industrial production. Summary of the invention
[0006] Therefore, the technical problem to be solved by the present invention is how to improve the catalyst activity while expanding the molecular weight distribution width of the produced polyethylene product, thereby providing a silica gel-supported nickel-vanadium bimetallic catalyst and its preparation method and application to achieve the above purpose.
[0007] A silica gel-supported nickel-vanadium bimetallic catalyst having a structure shown in the following formula 1:
[0008] Formula 1:
[0009] Among them, X, Y, R 1 –R 4 Each is independently selected from hydrogen, halogen or any one of the following groups: C1-6 Alkyl, C 1-6 Alkoxy, C 3-10 Cycloalkyl, C 3-10 Cycloalkyloxy, C 6-14 Aryl, C 6-14 Aryloxy.
[0010] R 1 –R 4 Each independently selected from hydrogen, fluorine, chlorine, bromine, C 1-6 Alkyl, C 3-10 Cycloalkyl or C 6-14 Aryl; or, X, Y, R 1 –R 4 Each is independently selected from any one of hydrogen, methyl, isopropyl, tert-butyl, fluorine, chlorine, methoxy, trifluoromethyl or cyclohexyl.
[0011] A method for preparing a silica gel-supported nickel-vanadium bimetallic catalyst comprises:
[0012] The silica gel and the vanadium source are immersed and stirred in a first solvent to obtain an immersed silica gel, the immersed silica gel is heat-treated to obtain a solid powder, and the solid powder is loaded with a nickel metal complex shown in Formula 2 to obtain a catalyst;
[0013] Formula 2: Among them, X, Y, R 1 –R 4 Same as the definition in claim 1 or 2.
[0014] The amount of the vanadium source added is 0.1-1wt% of the total weight of the silica gel according to the loading amount of the metal vanadium;
[0015] And / or, the amount of the nickel metal complex added is 0.1-1 wt % of the amount of silica gel, calculated on the basis of the loading amount of the metal nickel.
[0016] The first solvent is water or ethanol;
[0017] And / or, the vanadium source is a vanadium-containing substance soluble in the first solvent. Preferably, the vanadium source is one or more of ammonium metavanadate, vanadium nitrate, vanadium acetate, vanadium oxalate, vanadium phosphate, vanadium sulfate, vanadium oxysulfate, vanadium acetylacetonate, diacetylacetonate vanadium oxide, trichloro vanadium oxide, and tripropol vanadium oxide.
[0018] And / or, the dipping and stirring time is 1-12 hours, preferably 3-6 hours;
[0019] And / or, the temperature of the heat treatment is 500-1000°C, preferably 600-800°C;
[0020] And / or, the heat treatment time is 6-12h.
[0021] and / or, cooling under an inert atmosphere after the heat treatment;
[0022] And / or, the process of loading the nickel metal complex on the solid powder is: in an inert atmosphere, the solid powder is mixed with the second solvent and the nickel metal complex, stirred and the second solvent is evaporated to obtain the catalyst.
[0023] The inert atmosphere is a nitrogen atmosphere;
[0024] and / or, the treatment temperature of the stirring treatment is 35-60° C. and the treatment time is 2-10 h;
[0025] and / or, the evaporation temperature is 60-95°C;
[0026] And / or, the second solvent includes one or more of n-hexane, n-heptane, cyclohexane, n-pentane, methylcyclopentane, and methylcyclohexane.
[0027] The preparation method of the nickel metal complex comprises:
[0028] Acetyl α-diimine ligand of the structure shown in formula 3 is obtained, and the acenaphthenyl α-diimine ligand is mixed with a nickel source containing nickel dibromide to obtain a nickel metal complex shown in formula 2; the preparation process of the acenaphthenyl α-diimine ligand shown in formula 3 is: the compounds shown in formula 4 and formula 5 are subjected to a synthetic reaction to obtain the acenaphthenyl α-diimine ligand shown in formula 3;
[0029] Formula 3:
[0030] Formula 4:
[0031] Formula 5:
[0032] The solvent used in the synthesis reaction of the compounds represented by Formula 4 and Formula 5 is C 1-4 Alcohol, preferably including one or both of anhydrous methanol and anhydrous ethanol;
[0033] And / or, the solvent used in the step of mixing the acenaphthenyl α-diimine ligand with the nickel source containing nickel dibromide is one or more of tetrahydrofuran, anhydrous ether, pentane, cyclopentane, n-hexane, cyclohexane, heptane, methylcyclohexane, toluene, xylene, chlorobenzene, o-dichlorobenzene, o-xylene, and dichloromethane.
[0034] The invention also discloses the application of the silica gel supported nickel-vanadium bimetallic catalyst in ethylene polymerization reaction.
[0035] Alkyl aluminum is also added to the ethylene polymerization reaction, and the molar ratio of the alkyl aluminum to the nickel in the silica gel-supported nickel-vanadium bimetallic catalyst is 5-200:1; preferably, the molar ratio of the alkyl aluminum to the nickel in the silica gel-supported nickel-vanadium bimetallic catalyst is 10-100:1, and / or the alkyl aluminum is one or more of trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, diethyl aluminum monochloride, trioctylaluminum, methylaluminoxane, modified methylaluminoxane, and ethylaluminoxane;
[0036] And / or, the process of ethylene polymerization reaction is: ethylene is mixed with a third solvent, a comonomer, and an alkyl aluminum, and then a silica gel-supported nickel-vanadium bimetallic catalyst is added to carry out polymerization reaction; preferably, ethylene and / or the third solvent are first dehydrated and deoxygenated before being mixed with the comonomer, and / or, the polymerization reaction conditions are 60-150°C, 0.5-8MPa, 10-240min, and / or, the third solvent includes one or more of n-hexane, n-heptane, methylcyclohexane, toluene or cyclohexane, and / or, the comonomer includes one or more of 1-butene, 1-hexene or 1-octene.
[0037] The technical solution of the present invention has the following advantages:
[0038] 1. The silica gel-supported nickel-vanadium bimetallic catalyst provided by the present invention not only achieves the purpose of producing ethylene / α-olefin copolymers with a wider molecular weight distribution through the coordination of silica gel, vanadium and nickel metal complexes, but also effectively improves the catalyst activity, thereby achieving the purpose of taking into account both the product molecular weight distribution and the catalytic activity.
[0039] 2. The catalyst of the present invention has good stability, high polymerization activity, high economic added value and good industrialization prospects.
[0040] 3. In the application of the present invention, the molecular weight and molecular weight distribution can be easily adjusted by changing the amount of co-catalyst, polymerization temperature and molecular weight regulator, and the production flexibility is large, and multiple batches of products can be produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 The synthetic route of the silica gel supported nickel-vanadium bimetallic catalyst in the present invention is shown in FIG. DETAILED DESCRIPTION
[0043] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0044] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0045] Example 1
[0046] A silica gel supported nickel-vanadium bimetallic catalyst, the synthesis route of which is as follows Figure 1 As shown, the specific preparation process is as follows:
[0047] (1) obtaining raw materials having structures shown in Formula 4 and structures shown in Formula 5;
[0048] The structural raw materials shown in formula 4 are: The raw material of the structure shown in Formula 4 can be synthesized or purchased. In this embodiment, the raw material of the structure shown in Formula 4 was purchased from Anhui Dunmao New Material Technology Co., Ltd.;
[0049] The raw materials of the structure shown in Formula 5 are: 2,6-dimethylaniline and aniline.
[0050] (2) preparing an acenaphthene-based α-diimine ligand L1 having a structure shown in formula 3;
[0051] The compound of formula 3 was prepared according to the method in Organometallics, 2016, 11, 1794-1801. The specific process is as follows:
[0052] The compound of formula 4 is subjected to a synthesis reaction with 1 equiv. of 2,6-dimethylaniline of formula 5 and 1 equiv. of aniline of formula 5, respectively, to obtain the corresponding acenaphthene α-diimine ligand L1 of the structure shown in formula 3. The synthesis reaction process is: 2.5 mmol of the compound of formula 4 and 5.5 mmol of the compound of formula 5 are added to a round-bottom flask containing 25 ml of methanol, reacted at room temperature overnight under the catalysis of 0.1 ml of formic acid, filtered to obtain a yellow solid, and the yellow solid was washed with hot methanol to obtain the ligand L1.
[0053] Ligand L1: N,N-((2,6-diisopropylphenyl)imino)-4,7-dimethylacenaphthene, yield: 1.02 g, yield rate: 60%.
[0054] Rf = 0.50 (petroleum ether / dichloromethane, 1:2), its NMR data are:
[0055] 1 H NMR(CDCl3,400MHz): δ7.55(s,2H,aryl-H),7.34-7.16(m,6H,aryl-H),6.48(s,2H, aryl-H),3.19-2.87(dt,4H,CHMe2),2.3(s,6H,aryl-Me),1.4-0.8(dd,24H,CHMe2);
[0056] 13 C NMR(100MHz, CDCl3): δ161.48(N=C),147.66,138.25,138.09,135.56,131.32,1 29.46,127.29,124.48,124.33,123.44,28.66,23.53,23.24,22.46(aryl-Me).
[0057] Its mass spectrum data is: [M+H] + The calculated value is 529.3583 and the experimental value is 529.3572.
[0058] The elemental analysis data are: calculated value: C, 86.31; H, 8.39; N, 5.30; experimental value: C, 86.02; H, 8.19; N, 5.36.
[0059] (3) preparing a nickel metal complex C1 shown in formula 2;
[0060] The obtained ligand L1 (0.49 mmol) and 1 equiv. of (DME)NiBr2 (0.49 mmol) were added into a solvent storage bottle containing 10 ml of dichloromethane, reacted at room temperature overnight, drained, washed 4 times with 20 mL of ether and then vacuum dried to obtain the nickel metal complex C1 with the structure shown in Formula 2.
[0061] C1: (4,7-diMeN^N)NiBr2, yield 0.275 g, yield 75%.
[0062] Its mass spectrum data is: [M-Br]+ experimental value is 665.0144.
[0063] The elemental analysis data are: calculated value: C, 61.08; H, 5.93; N, 3.75; experimental value: C, 61.28; H, 5.71; N, 3.46.
[0064] (4) preparing a silica gel-supported nickel-vanadium bimetallic catalyst;
[0065] Weigh 10 g of Grace Davison 955 silica gel, place the silica gel in an ammonium metavanadate aqueous solution at 35° C. and immerse and stir for 3 hours; the amount of ammonium metavanadate used is 0.15 wt% (34.5 mg) of the silica gel mass based on the vanadium loading amount, then evaporate the aqueous solution at 120° C. and dry to obtain the impregnated silica gel;
[0066] In an air atmosphere, the impregnated silica gel was calcined at 600°C in a fluidized bed for 8 hours, and then the heating was turned off and switched to a nitrogen atmosphere, and cooled to room temperature to obtain a solid powder.
[0067] Under the protection of high-purity nitrogen, firstly transfer 5 g of solid powder into a container, add 150 mL of refined n-hexane as solvent with a syringe, add nickel metal complex C1 (153.0 mg) in an amount of 0.27 wt% of the mass of the solid powder, based on the nickel loading, adjust the temperature to 45°C, stir continuously at the constant temperature for 5 hours, then raise the temperature to 80°C, and increase the nitrogen flow rate at the same time. After the n-hexane is completely evaporated, a silica gel-supported nickel-vanadium bimetallic catalyst is obtained, which is recorded as Cat1.
[0068] Example 2
[0069] A silica gel supported nickel-vanadium bimetallic catalyst, the synthesis route of which is as follows Figure 1 As shown, the specific preparation process is as follows:
[0070] (1) obtaining raw materials having structures shown in Formula 4 and structures shown in Formula 5;
[0071] The structural raw materials shown in formula 4 are: The raw material of the structure shown in Formula 4 can be synthesized or purchased. In this embodiment, the raw material of the structure shown in Formula 4 was purchased from Anhui Dunmao New Material Technology Co., Ltd.;
[0072] The raw materials of the structure shown in Formula 5 are: 2,6-diisopropylaniline and aniline.
[0073] (2) preparing an acenaphthene-based α-diimine ligand L2 having a structure shown in formula 3;
[0074] The compound of formula 3 was prepared according to the method in Organometallics, 2016, 11, 1794-1801. The specific process is as follows:
[0075] The compound shown in Formula 4 is subjected to a synthesis reaction with 1 equiv. of 2,6-diisopropylaniline shown in Formula 5 and 1 equiv. of aniline shown in Formula 5, respectively, to obtain the corresponding acenaphthene α-diimine ligand L2 having the structure shown in Formula 3. The synthesis reaction process is as follows: 2.5 mmol of the compound shown in Formula 4 and 5.5 mmol of the compound shown in Formula 5 are added to a round-bottom flask containing 25 ml of methanol, reacted at room temperature overnight under the catalysis of 0.1 ml of formic acid, filtered to obtain a yellow solid, and the yellow solid is washed with methanol to obtain the ligand L2.
[0076] Ligand L2: N,N-((2,6-diisopropylphenyl)imino)-5-methoxyacenaphthene, yield: 0.86 g, yield rate: 65%.
[0077] Rf = 0.40 (ethyl acetate / petroleum ether, 1:20), its NMR data are:
[0078] 1H NMR (CDCl3, 400MHz): δ8.09 (d, J=8.3Hz, 1H, aryl-H), 7.44-7.23 (m, 6H, aryl-H), 7.23 (s, 1H, aryl-H), 6 .77-6.52(m,3H,aryl-H),3.97(s,3H,aryl-OMe),3.20-2.73(m,4H,CHMe2),1.38-0.84(m,24H,CHMe2);
[0079] 13 C NMR (100MHz, CDCl3): δ161.80(N=C), 160.40(N=C), 157.54(O-Caryl), 135.92, 126.97, 125.16, 124.37, 124. 31,124.12,124.03,123.54,123.50,123.15,105.79,55.96(OMe),28.70,28.65,23.63,23.54,23.31,23.25.
[0080] Its mass spectrum data are: [M+H]+ calculated value is 531.3375, experimental value is 531.3368.
[0081] The elemental analysis data are: calculated value: C, 83.73; H, 7.98; N, 5.28; experimental value: C, 83.45; H, 7.78; N, 5.31.
[0082] (3) preparing a nickel metal complex C2 shown in formula 2;
[0083] The obtained ligand L2 (0.49 mmol) and 1 equiv. of (DME)NiBr2 (0.49 mmol) were added into a solvent storage bottle containing 10 ml of dichloromethane, reacted at room temperature overnight, drained, washed 4 times with 20 mL of ether and then vacuum dried to obtain the nickel metal complex C2 with the structure shown in Formula 2.
[0084] C2: (5-OMeN^N)NiBr2, yield is 0.307g, yield rate is 80%.
[0085] Its mass spectrum data is: [M-Br]+ experimental value is 667.0510.
[0086] The elemental analysis data are: calculated value: C, 59.31; H, 5.65; N, 3.74; experimental value: C, 59.53; H, 5.92; N, 3.48.
[0087] (4) Preparation of silica gel supported nickel-vanadium bimetallic catalyst
[0088] Weigh 10 g of Grace Davison 945 silica gel, place the silica gel in a vanadium nitrate aqueous solution at 40° C. and immerse and stir for 4 hours; the amount of vanadium nitrate used is 0.3 wt% (212.6 mg) of the silica gel mass based on the vanadium loading amount, then evaporate the aqueous solution at 115° C. and dry to obtain the impregnated silica gel;
[0089] In an air atmosphere, the impregnated silica gel was calcined at 700°C in a fluidized bed for 9 hours, and then the heating was turned off and switched to a nitrogen atmosphere, and cooled to room temperature to obtain a solid powder.
[0090] Under the protection of high-purity nitrogen, first transfer 5 g of solid powder into a container, add 150 mL of refined n-hexane as a solvent with a syringe, add nickel metal complex C2 (170.5 mg) in an amount of 0.3 wt% of the mass of the silica gel-supported vanadium catalyst, based on the nickel loading, adjust the temperature to 50°C, stir continuously at a constant temperature for 6 hours, then raise the temperature to 85°C, and increase the nitrogen flow rate at the same time. After the n-hexane is completely evaporated, a silica gel-supported nickel-vanadium bimetallic catalyst is obtained, which is recorded as Cat2.
[0091] Example 3
[0092] A silica gel supported nickel-vanadium bimetallic catalyst, the synthesis route of which is as follows Figure 1 As shown, the specific preparation process is as follows:
[0093] (1) obtaining raw materials having structures shown in Formula 4 and structures shown in Formula 5;
[0094] The structural raw materials shown in formula 4 are: The raw material of the structure shown in Formula 4 can be synthesized or purchased. In this embodiment, the raw material of the structure shown in Formula 4 was purchased from Anhui Dunmao New Material Technology Co., Ltd.;
[0095] The raw materials of the structure shown in Formula 5 are: 2,6-diisopropylaniline and aniline.
[0096] (2) preparing an acenaphthene-based α-diimine ligand L3 having a structure shown in formula 3;
[0097] The compound of formula 3 was prepared according to the method in Organometallics, 2016, 11, 1794-1801. The specific process is as follows:
[0098] The compound shown in Formula 4 is subjected to a synthesis reaction with 1 equiv. of 2,6-diisopropylaniline shown in Formula 5 and 1 equiv. of aniline shown in Formula 5, respectively, to obtain the corresponding acenaphthene α-diimine ligand L3 having the structure shown in Formula 3. The synthesis reaction process is as follows: the raw materials are added to a round-bottom flask containing 25 ml of methanol, reacted at room temperature overnight under the catalysis of 0.1 ml of formic acid, filtered to obtain a yellow solid, and the yellow solid is washed with hot methanol to obtain the ligand L3.
[0099] Ligand L3: N,N-((2,6-diisopropylphenyl)imino)-5,6-dimethylacenaphthene, yield: 0.84 g, yield rate: 60%.
[0100] Rf = 0.30 (ethyl acetate / petroleum ether, 1:20), its NMR data are:
[0101] 1 H NMR (CDCl3, 400MHz): δ7.21 (dt, J=18.7, 8.7Hz, 6H, aryl-H), 6.58 (q, J=8.2Hz, aryl- H),3.9(s,6H,aryl-OMe),2.98(dt,J=13.6,6.8Hz,4H,CHMe2),1.11(dd,24H,CHMe2);
[0102] 13 C NMR (100MHz, CDCl3): δ160.77 (N=C), 159.07 (O-Caryl), 147.88, 145.53, 135.82, 125.8 0,124.37,123.97,123.43,122.24,114.66,106.52,56.33(OMe),28.60,23.61,23.29.
[0103] Its mass spectrum data is: [M+H] +The calculated value is 561.3481 and the experimental value is 561.3463.
[0104] The elemental analysis data are: calculated value: C, 81.39; H, 7.91; N, 5.00; experimental value: C, 81.08; H, 7.66; N, 4.96.
[0105] (3) preparing a nickel metal complex C3 shown in formula 2;
[0106] The obtained ligand L3 (0.49 mmol) and 1 equiv. of (DME)NiBr2 (0.49 mmol) were added into a solvent storage bottle containing 10 ml of dichloromethane, reacted at room temperature overnight, drained, washed 4 times with 20 mL of ether and then vacuum dried to obtain the nickel metal complex C3 with the structure shown in Formula 2.
[0107] C3: (5,6-diOMeN^N)NiBr2, yield 0.326 g, yield rate 85%.
[0108] Its mass spectrum data is: [M-Br]+ experimental value is 697.0929.
[0109] The elemental analysis data are: calculated value: C, 58.57; H, 5.69; N, 3.59; experimental value: C, 58.75; H, 5.73; N, 3.47.
[0110] (4) Preparation of silica gel supported nickel-vanadium bimetallic catalyst
[0111] Weigh 10 g of PQ CS-2133 silica gel, place the silica gel in a vanadyl oxalate aqueous solution at 45° C. and immerse and stir for 5 hours; the amount of vanadyl oxalate used is 0.5 wt% (152.1 mg) of the silica gel mass based on the vanadium loading amount, then evaporate the aqueous solution at 115° C. and dry to obtain the impregnated silica gel;
[0112] In an air atmosphere, the impregnated silica gel was calcined at 800°C in a fluidized bed for 6 hours, and then the heating was turned off and switched to a nitrogen atmosphere, and cooled to room temperature to obtain a solid powder.
[0113] Under the protection of high-purity nitrogen, first transfer 5g of solid powder to a container, add 150mL of refined n-hexane as solvent with a syringe, add 0.45wt% of the mass of the solid powder based on the nickel loading of the nickel metal complex C3 (267.2mg), adjust the temperature to 60°C, and stir continuously at constant temperature for 3h. Then raise the temperature to 90°C, and increase the nitrogen flow rate at the same time. After the n-hexane is completely evaporated, a solid powder is obtained, which is a silica gel-supported nickel-vanadium bimetallic catalyst, recorded as Cat3.
[0114] Example 4
[0115] A silica gel supported nickel-vanadium bimetallic catalyst, the synthesis route of which is as follows Figure 1 As shown, the specific preparation process is as follows:
[0116] (1) obtaining raw materials having structures shown in Formula 4 and structures shown in Formula 5;
[0117] The structural raw materials shown in formula 4 are: The raw material of the structure shown in Formula 4 can be synthesized or purchased. In this embodiment, the raw material of the structure shown in Formula 4 was purchased from Anhui Dunmao New Material Technology Co., Ltd.;
[0118] The raw materials of the structure shown in Formula 5 are: 2,6-diisopropylaniline and aniline.
[0119] (2) preparing an acenaphthene-based α-diimine ligand L4 having a structure shown in formula 3;
[0120] The compound of formula 3 was prepared according to the method in Organometallics, 2016, 11, 1794-1801. The specific process is as follows:
[0121] The compound shown in Formula 4 is subjected to a synthesis reaction with 1 equiv. of 2,6-diisopropylaniline shown in Formula 5 and 1 equiv. of aniline shown in Formula 5, respectively, to obtain the corresponding acenaphthene α-diimine ligand L4 having the structure shown in Formula 3. The synthesis reaction process is as follows: the raw materials are added to a round-bottom flask containing 25 ml of methanol, reacted at room temperature overnight under the catalysis of 0.1 ml of formic acid, filtered to obtain a yellow solid, and the yellow solid is washed with hot methanol to obtain the ligand L4.
[0122] Ligand L4: N,N-((2,6-diisopropylphenyl)imino)-3-methoxyacenaphthene, yield: 0.86 g, yield rate: 65%.
[0123] Rf = 0.30 (ethyl acetate / petroleum ether, 1:20), its NMR data are:
[0124] 1 H NMR (CDCl3, 400MHz): δ7.93 (d, J=8.9Hz, 1H, aryl-H), 7.79 (d, J=8.2Hz, aryl-H), 7.23 (s, 1H, aryl-H), 7.05-7.23 (m, 6H, aryl-H), 7.06 (s, 1H, a ryl-H),6.57(s,1H,aryl-H),4.19,3.29(s,3H,aryl-OMe),2.96(td,4H,CHMe2),1.21(d,J=6.8Hz,12H,CHMe2),0.97(d,J=12.1Hz,12H,CHMe2);
[0125] 13 C NMR (100MHz, CDCl3): δ161.70 (N=C), 160.20 (N=C), 158.49 (OC aryl ),136.87,125.97,124.98,124.37,124.35,124.12,124.13,123.57,123.50,123.16,105.79,56.56(OMe),28.70,28.65,23.63,23.55,23.33,23.27. Its mass spectrum data is: [M+H] + The calculated value is 531.3375 and the experimental value is 531.3385.
[0126] The elemental analysis data are: calculated value: C, 83.73; H, 7.98; N, 5.28; experimental value: C, 83.51; H, 7.93; N, 5.37.
[0127] (3) preparing a nickel metal complex C4 shown in formula 2;
[0128] The obtained ligand L4 (0.49 mmol) and 1 equiv. of (DME)NiBr2 (0.49 mmol) were added into a solvent storage bottle containing 10 ml of dichloromethane, reacted at room temperature overnight, drained, washed 4 times with 20 mL of ether and then vacuum dried to obtain the nickel metal complex C4 with the structure shown in Formula 2.
[0129] C4: (3-OMeN^N)NiBr2, yield is 0.338g, yield rate is 88%.
[0130] Its mass spectrum data is: [M-Br]+ experimental value is 667.0696.
[0131] The elemental analysis data are: calculated value: C, 59.31; H, 5.65; N, 3.74; experimental value: C, 59.45; H, 5.81; N, 3.56.
[0132] (4) preparing a silica gel-supported nickel-vanadium bimetallic catalyst;
[0133] Weigh 10 g of Grace Davison 955 silica gel, place the silica gel in a vanadium nitrate aqueous solution at 40° C. and immerse and stir for 6 hours; the amount of vanadium nitrate used is 0.2 wt% (141.7 mg) of the silica gel mass based on the vanadium loading amount, then evaporate the aqueous solution at 115° C. and dry to obtain the impregnated silica gel;
[0134] In an air atmosphere, the impregnated silica gel was calcined at 600°C in a fluidized bed for 8 hours, and then the heating was turned off and switched to a nitrogen atmosphere, and cooled to room temperature to obtain a solid powder.
[0135] Under the protection of high-purity nitrogen, first transfer 5g of solid powder to a container, add 150mL of refined n-hexane as solvent with a syringe, add 0.25wt% of the nickel metal complex C4 (142.1mg) based on the nickel loading amount of the solid powder, adjust the temperature to 40°C, and stir continuously at constant temperature for 5h. Then raise the temperature to 75°C, and increase the nitrogen flow rate at the same time. After the n-hexane is completely evaporated, a solid powder is obtained, which is a silica gel-supported nickel-vanadium bimetallic catalyst, recorded as Cat4.
[0136] Example 5
[0137] The difference from Example 2 is that step (4) is different. The specific process for preparing the silica gel-supported nickel-vanadium bimetallic catalyst is as follows:
[0138] Weigh 10 g of PQ CS-2040 silica gel, place the silica gel in an aqueous solution of ammonium metavanadate at 30° C. and immerse and stir for 5 hours; the amount of ammonium metavanadate used is 0.35 wt% (80.4 mg) of the silica gel mass based on the vanadium loading amount, then evaporate the aqueous solution at 115° C. and dry to obtain the impregnated silica gel;
[0139] In an air atmosphere, the impregnated silica gel was calcined at 650°C in a fluidized bed for 12 hours, and then the heating was turned off and switched to a nitrogen atmosphere, and cooled to room temperature to obtain a solid powder.
[0140] Under the protection of high-purity nitrogen, 5 g of solid powder was first transferred to a container, 150 mL of refined n-hexane was added as a solvent by a syringe, and 0.6 wt% of the mass of the solid powder was added in terms of the nickel loading of the nickel metal complex C2 (340.9 mg), the temperature was adjusted to 40°C, and the mixture was stirred continuously at the constant temperature for 5 hours. Then the temperature was raised to 70°C, and the nitrogen flow rate was increased at the same time. After the n-hexane was completely evaporated, a solid powder was obtained, which was a silica gel-supported nickel-vanadium bimetallic catalyst, recorded as Cat5.
[0141] Example 6
[0142] The difference from Example 3 is that step (4) is different. The specific process for preparing the silica gel-supported nickel-vanadium bimetallic catalyst is as follows:
[0143] Weigh 10g of PQ CS-2040 silica gel, place the silica gel in an aqueous solution of ammonium metavanadate and immerse and stir for 3h at 35°C; the amount of ammonium metavanadate used is 0.27wt% of the mass of the silica gel based on the vanadium loading.
[0144] (62 mg), then the aqueous solution was evaporated at 120°C and dried to obtain the impregnated silica gel;
[0145] In an air atmosphere, the impregnated silica gel was calcined at 900°C in a fluidized bed for 6 hours, and then the heating was turned off and switched to a nitrogen atmosphere, and cooled to room temperature to obtain a solid powder.
[0146] Under the protection of high-purity nitrogen, 5g of solid powder was first transferred to a container, 150mL of refined n-hexane was added as a solvent by a syringe, and 0.6wt% of the mass of the solid powder was added in terms of nickel loading, nickel metal complex C3 (356.3mg), the temperature was adjusted to 40°C, and the mixture was stirred continuously at constant temperature for 5h. Then the temperature was raised to 75°C, and the nitrogen flow rate was increased at the same time. After the n-hexane was completely evaporated, a solid powder was obtained, which was a silica gel-supported nickel-vanadium bimetallic catalyst, recorded as Cat6.
[0147] Example 7
[0148] The difference from Example 6 is that step (4) is different. The specific process for preparing the silica gel-supported nickel-vanadium bimetallic catalyst is as follows:
[0149] Weigh 10g of PQ CS-2040 silica gel, place the silica gel in an aqueous solution of ammonium metavanadate and immerse and stir for 3h at 35°C; the amount of ammonium metavanadate used is 0.95wt% of the silica gel mass based on the vanadium loading.
[0150] (218 mg), then the aqueous solution was evaporated at 120°C and dried to obtain the impregnated silica gel;
[0151] In an air atmosphere, the impregnated silica gel was calcined at 900°C in a fluidized bed for 6 hours, and then the heating was turned off and switched to a nitrogen atmosphere, and cooled to room temperature to obtain a solid powder.
[0152] Under the protection of high-purity nitrogen, 5 g of solid powder was first transferred to a container, 150 mL of refined n-hexane was added as a solvent by a syringe, and 0.9 wt% of the mass of the solid powder was added in terms of the nickel loading amount of the nickel metal complex C3 (534.5 mg), the temperature was adjusted to 40°C, and the mixture was stirred continuously at the constant temperature for 5 hours. Then the temperature was raised to 75°C, and the nitrogen flow rate was increased at the same time. After the n-hexane was completely evaporated, a solid powder was obtained, which was a silica gel-supported nickel-vanadium bimetallic catalyst, denoted as Cat7.
[0153] Example 8
[0154] The catalytic application of silica gel supported nickel-vanadium bimetallic catalyst Cat1 in ethylene polymerization is as follows:
[0155] A 500ml reactor was heated to 130°C and vacuumed for 2h, during which nitrogen was replaced three times, and then vacuumed and filled with ethylene twice. After the temperature was cooled to room temperature, 150ml of dehydrated and deoxygenated n-heptane and 50ml of 1-hexene were added. When the temperature of the reactor was stabilized at 90°C, 0.16mL, 1.1mol / L of triisobutylaluminum n-hexane solution and 200mg of catalyst Cat1 were added according to Al / Cr=30, stirred, and 1MPa of ethylene was introduced for polymerization reaction. After the reaction for 60min, the ethylene inlet valve was closed, the temperature was rapidly cooled with a low-temperature circulating water bath, the pressure was slowly released, and the reactor was unloaded to obtain the product (POP). After drying and weighing analysis, it was found that:
[0156] Polymerization activity = 2200 kg POP (mol Ni) -1 h -1 , POP melting point is 95℃, weight average molecular weight Mw=12.6*10 4 g / mol, molecular weight distribution index PDI = 16.5. HT 13C-NMR characterization revealed that the 1-hexene insertion rate was 16.98%.
[0157] Example 9
[0158] The catalytic application of silica gel supported nickel-vanadium bimetallic catalyst Cat2 in ethylene polymerization is as follows:
[0159] Heat a 500ml reactor to 120°C and evacuate for 3h, during which nitrogen is replaced three times, then evacuate and charge ethylene twice, wait until the temperature cools to room temperature, add 140ml of dehydrated and deoxygenated n-heptane and 60ml of 1-octene, and when the temperature of the reactor stabilizes at 100°C, add 0.09mL, 1.1mol / L of triisobutylaluminum n-hexane solution and 200mg of catalyst Cat2 according to Al / Cr=15, stir, and introduce 1.5MPa of ethylene for polymerization. After reacting for 60min, close the ethylene inlet valve, cool rapidly with a low-temperature circulating water bath, slowly release the pressure, unload the reactor to obtain the product polyethylene, dry and weigh for analysis, and the following is known:
[0160] Polymerization activity = 1900 kg POP (mol Ni) -1 h -1 , POP melting point = 89 ° C, weight average molecular weight Mw = 8.1*10 4 g / mol, molecular weight distribution index PDI = 12.2. HT 13C-NMR characterization revealed that the 1-octene insertion rate was 15.28%.
[0161] Example 10
[0162] The catalytic application of silica gel supported nickel-vanadium bimetallic catalyst Cat3 in ethylene polymerization is as follows:
[0163] Heat a 500ml reactor to 110°C and evacuate for 4h, during which nitrogen is replaced three times, then evacuate and charge ethylene twice, wait until the temperature cools to room temperature, add 140ml of dehydrated and deoxygenated n-heptane and 60ml of 1-hexene, and when the temperature of the reactor stabilizes at 100°C, add 0.45mL, 1.1mol / L trioctyl aluminum n-hexane solution and 200mg of catalyst Cat3 according to Al / Cr=50, stir, and introduce 1MPa ethylene for polymerization. After 60min of reaction, close the ethylene inlet valve, cool rapidly with a low-temperature circulating water bath, slowly release the pressure, unload the reactor to obtain the product polyethylene, dry and weigh for analysis, and it can be seen that:
[0164] Polymerization activity = 1100 kg PE (mol Ni) -1 h -1 , POP melting point = 91 ° C, weight average molecular weight Mw = 9.3*10 4 g / mol, molecular weight distribution index PDI = 11.3. HT 13C-NMR characterization revealed that the 1-hexene insertion rate was 19.76%.
[0165] Embodiment 11
[0166] The catalytic application of silica gel supported nickel-vanadium bimetallic catalyst Cat4 in ethylene polymerization is as follows:
[0167] A 500ml reactor was heated to 125°C and vacuumed for 4h, during which nitrogen was replaced three times, and then vacuumed and filled with ethylene twice. After the temperature was cooled to room temperature, 150ml of dehydrated and deoxygenated n-heptane and 50ml of 1-octene were added. When the temperature of the reactor was stabilized at 100°C, 0.4mL of 1.1mol / L diethylaluminum chloride toluene solution and 200mg of catalyst Cat4 were added according to Al / Cr=80, and 3MPa of ethylene was introduced for polymerization. After the reaction for 60min, the ethylene inlet valve was closed, the temperature was rapidly reduced with a low-temperature circulating water bath, the pressure was slowly released, and the product polyethylene was unloaded to obtain the product. After drying and weighing analysis, it was found that:
[0168] Polymerization activity = 1700 kg POP (mol Ni) -1 h -1 , PE melting point = 92 ° C, weight average molecular weight Mw = 11.5*10 4 g / mol, molecular weight distribution index PDI = 11.7. HT 13C-NMR characterization revealed that the 1-octene insertion rate was 13.79%.
[0169] Example 12
[0170] The catalytic application of silica gel supported nickel-vanadium bimetallic catalyst Cat5 in ethylene polymerization is as follows:
[0171] A 500ml reactor was heated to 115°C and vacuumed for 4h, during which nitrogen was replaced three times, and then vacuumed and filled with ethylene twice. After the temperature was cooled to room temperature, 140ml of dehydrated and deoxygenated n-heptane and 60ml of 1-hexene were added. When the temperature of the reactor was stabilized at 100°C, 0.72ml of 1.1mol / L trioctyl aluminum heptane solution and 200mg of catalyst Cat5 were added according to Al / Cr=60, stirred, and 3MPa of ethylene was introduced for polymerization reaction. After the reaction for 60min, the ethylene inlet valve was closed, the temperature was rapidly reduced with a low-temperature circulating water bath, the pressure was slowly released, and the product polyethylene was unloaded to obtain. After drying and weighing analysis, it was found that:
[0172] Polymerization activity = 1600 kg POP (mol Ni) -1 h -1 , POP melting point = 87 ° C, weight average molecular weight Mw = 9.5*10 4 g / mol, molecular weight distribution index PDI = 11.9. HT 13C-NMR characterization revealed that the 1-hexene insertion rate was 17.53%.
[0173] Example 13
[0174] The catalytic application of silica gel supported nickel-vanadium bimetallic catalyst Cat6 in ethylene polymerization is as follows:
[0175] Heat a 500ml reactor to 125°C and evacuate for 4h, during which nitrogen is replaced three times, then evacuate and charge ethylene twice, wait until the temperature cools to room temperature, add 140ml of dehydrated and deoxygenated cyclohexane and 60ml of 1-hexene, and when the temperature of the reactor stabilizes at 100°C, add 1.08ml of 1.1mol / L triethylaluminum toluene solution and 200mg of catalyst Cat6 according to Al / Cr=90, stir, and introduce 6MPa of ethylene for polymerization. After reacting for 30min, close the ethylene inlet valve, cool rapidly with a low-temperature circulating water bath, slowly release the pressure, unload the reactor to obtain the product polyethylene, dry and weigh for analysis, and the following is obtained:
[0176] Polymerization activity = 2300 kg POP (mol Ni) -1 h -1 , POP melting point = 91 ° C, weight average molecular weight = 7.1*10 4 g / mol, molecular weight distribution index PDI = 10.8. HT 13C-NMR characterization revealed that the 1-hexene insertion rate was 18.22%.
[0177] Embodiment 14
[0178] The catalytic application of silica gel supported nickel-vanadium bimetallic catalyst Cat7 in ethylene polymerization is as follows:
[0179] Heat a 500ml reactor to 125°C and evacuate for 4h, replace with nitrogen three times, then evacuate and charge with ethylene twice, wait until the temperature is cooled to room temperature, add 140ml of dehydrated and deoxygenated cyclohexane and 60ml of 1-hexene, when the temperature of the reactor is stabilized at 100°C, add 1.08ml of 1.1mol / L triethylaluminum toluene solution and 200mg of catalyst Cat7 according to Al / Cr=90, stir, pass 5MPa of ethylene to carry out polymerization reaction, react for 45min, close the ethylene inlet valve, cool rapidly with a low-temperature circulating water bath, slowly release the pressure, unload the reactor to obtain the product polyethylene, dry and weigh and analyze, and it is found that:
[0180] Polymerization activity = 1650 kg POP (mol Ni) -1 h -1 , POP melting point = 103 ° C, weight average molecular weight = 9.3*10 4 g / mol, molecular weight distribution index PDI = 11.5. HT 13C-NMR characterization revealed that the 1-hexene insertion rate was 13.17%.
[0181] Comparative Example 1
[0182] The difference between this comparative example and Example 10 is that the catalyst type is different, and the rest is exactly the same as Example 10. Specifically, in this comparative example, silica gel-supported vanadium nickel catalyst (Ni / V-SiO2) is used to replace silica gel-supported nickel-vanadium bimetallic catalyst Cat1. The specific preparation process of silica gel-supported vanadium nickel catalyst (Ni / V-SiO2) in this comparative example is as follows:
[0183] 1) Weigh 10g of Grace Davison 955 silica gel, and immerse and stir the silica gel in an aqueous solution of ammonium metavanadate and nickel carbonate at 35°C for 3h; the amount of ammonium metavanadate used is 0.15wt% (34.5mg) of the silica gel mass based on the vanadium loading, and the amount of nickel carbonate used is 0.27wt% (30.3mg) of the silica gel mass based on the nickel loading, then evaporate the aqueous solution at 120°C and dry to obtain a solid powder; 2) Under air atmosphere, calcine the solid powder at 600°C in a fluidized bed for 8h, then turn off the heating, switch to a nitrogen atmosphere, and cool to room temperature to obtain a silica gel-supported vanadium chromium catalyst.
[0184] The experimental results of this comparative example are as follows:
[0185] Polymerization activity = 630 kg POP (mol Cr) -1 h -1 , POP melting point is 115℃, weight average molecular weight Mw=15.9*10 4g / mol, molecular weight distribution index PDI = 13.2. HT 13C-NMR characterization revealed that the 1-octene insertion rate was 1.19%.
[0186] Comparative Example 2
[0187] The difference between this comparative example and Example 7 is that the catalyst type is different, and the rest is exactly the same as Example 7. Specifically, in this comparative example, a vanadium-free silica gel-supported nickel metal catalyst Cat8 is used to replace the silica gel-supported nickel-vanadium bimetallic catalyst Cat1. The specific preparation process of the silica gel-supported nickel bimetallic catalyst Cat8 in this comparative example is as follows:
[0188] Weigh 10g of Grace Davison 955 silica gel, calcine it at 600℃ in a fluidized bed for 8h, then turn off the heating, switch to nitrogen atmosphere, and cool to room temperature to obtain a solid powder; under the protection of high-purity nitrogen, first transfer 5g of the solid powder to a container, add 150mL of refined n-hexane as a solvent with a syringe, add 0.27wt% of the nickel metal complex C1 (153.0mg) based on the nickel loading amount of the silica gel-supported vanadium catalyst mass, adjust the temperature to 45℃, stir continuously at a constant temperature for 5h, then raise the temperature to 80℃, and increase the nitrogen flow rate at the same time. After the n-hexane is completely evaporated, a silica gel-supported nickel metal catalyst is obtained, which is recorded as Cat8.
[0189] The experimental results of this comparative example are as follows:
[0190] Polymerization activity = 630 kg POP (mol Cr) -1 h -1 , POP melting point is 115℃, weight average molecular weight Mw=15.9*10 4 g / mol, molecular weight distribution index PDI = 13.2. HT 13C-NMR characterization revealed that the 1-octene insertion rate was 1.19%.
[0191] Comparative Example 3
[0192] The difference between this comparative example and Example 7 is that the catalyst type is different, and the rest is exactly the same as Example 7. Specifically, in this comparative example, the silica gel-supported nickel-manganese bimetallic catalyst Cat9 is used to replace the silica gel-supported nickel-vanadium bimetallic catalyst Cat1. The specific preparation process of the silica gel-supported nickel-manganese bimetallic catalyst Cat9 in this comparative example is as follows:
[0193] Weigh 10 g of Grace Davison 955 silica gel, place the silica gel in a manganese acetate aqueous solution at 35° C. and immerse and stir for 3 hours; the amount of manganese acetate used is 0.15 wt% (47.3 mg) of the mass of the silica gel based on the manganese loading, then evaporate the aqueous solution at 120° C. and dry to obtain the impregnated silica gel;
[0194] In an air atmosphere, the impregnated silica gel was calcined at 600°C in a fluidized bed for 8 hours, and then the heating was turned off and switched to a nitrogen atmosphere, and cooled to room temperature to obtain a solid powder.
[0195] Under the protection of high-purity nitrogen, firstly, 5 g of solid powder was transferred into a container, 150 mL of refined n-hexane was added as a solvent with a syringe, and 0.27 wt% of the nickel metal complex C1 (153.0 mg) was added based on the nickel loading amount of the solid powder. The temperature was adjusted to 45°C, and the mixture was stirred continuously at the constant temperature for 5 h. Then, the temperature was raised to 80°C, and the nitrogen flow rate was increased. After the n-hexane was completely evaporated, a silica gel-supported nickel-manganese bimetallic catalyst was obtained, which was recorded as Cat9.
[0196] The experimental results of this comparative example are as follows:
[0197] Polymerization activity = 1580 kg POP (mol Cr) -1 h -1 , POP melting point is 93℃, weight average molecular weight Mw=15.4*10 4 g / mol, molecular weight distribution index PDI = 11.7. HT 13C-NMR characterization revealed that the 1-octene insertion rate was 16.15%.
[0198] According to the data comparison of the above examples 8-14 and comparative example 1, it can be seen that the homopolymerization activity of the silica gel-supported nickel-vanadium bimetallic catalyst in the embodiments of the present invention can reach 1100 kg POP (mol Cr) -1 h -1 Above, up to 2300kg POP (mol Cr) -1 h -1 , significantly better than the 630kg POP (mol Cr) of silica gel supported vanadium nickel catalyst (Ni / V-SiO2) -1 h -1 .
[0199] According to the data of the above-mentioned Example 8 and Comparative Examples 2-3, it can be known that the silica gel-supported nickel metal catalyst cat8, which directly adopts silica gel and nickel metal complex C, can have a high catalytic activity, but its molecular weight distribution range is narrow; although the molecular weight distribution range can be effectively widened by adding metal Mn salt, see the results of silica gel-supported nickel manganese bimetallic catalyst Cat9 in Comparative Example 3, its catalytic activity is significantly reduced. Compared with the vanadium-free silica gel-supported nickel metal catalyst cat8, the silica gel-supported nickel vanadium bimetallic catalyst cat1 in the present invention can not only produce ethylene polymers with a wide molecular weight distribution, but also improve the catalytic activity of the catalyst and have good copolymerization performance.
[0200] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.
Claims
1. A silica gel supported nickel-vanadium bimetallic catalyst, characterized in that: It has the structure shown in the following formula 1: Formula 1: Among them, X, Y, R 1 –R 4 Each is independently selected from hydrogen, halogen or any one of the following groups: C 1-6 Alkyl, C 1-6 Alkoxy, C 3-10 Cycloalkyl, C 3-10 Cycloalkyloxy, C 6-14 Aryl, C 6-14 Aryloxy.
2. The silica gel-supported nickel-vanadium bimetallic catalyst according to claim 1, characterized in that: R 1 –R 4 Each independently selected from hydrogen, fluorine, chlorine, bromine, C 1-6 Alkyl, C 3-10 Cycloalkyl or C 6-14 Aryl; or, X, Y, R 1 –R 4 Each is independently selected from any one of hydrogen, methyl, isopropyl, tert-butyl, fluorine, chlorine, methoxy, trifluoromethyl or cyclohexyl.
3. A method for preparing a silica gel-supported nickel-vanadium bimetallic catalyst, characterized in that: include: The silica gel and the vanadium source are immersed and stirred in a first solvent to obtain an immersed silica gel, the immersed silica gel is heat-treated to obtain a solid powder, and the solid powder is loaded with a nickel metal complex shown in Formula 2 to obtain a catalyst; Formula 2: Among them, X, Y, R 1 –R 4 Same as the definition in claim 1 or 2.
4. The preparation method according to claim 3, characterized in that: The amount of the vanadium source added is 0.1-1wt% of the total weight of the silica gel according to the loading amount of the metal vanadium; And / or, the amount of the nickel metal complex added is 0.1-1 wt % of the amount of silica gel, calculated on the basis of the loading amount of the metal nickel.
5. The preparation method according to claim 3 or 4, characterized in that: The first solvent is water or ethanol; And / or, the vanadium source is a vanadium-containing substance soluble in the first solvent, preferably, the vanadium source is one or more of ammonium metavanadate, vanadium nitrate, vanadium acetate, vanadyl oxalate, vanadium phosphate, vanadium sulfate, vanadyl sulfate, vanadium acetylacetonate, vanadium diacetylacetonate oxide, vanadium trichloride oxide, and vanadium tripropoxide oxide; And / or, the dipping and stirring time is 1-12 hours, preferably 3-6 hours; And / or, the temperature of the heat treatment is 500-1000°C, preferably 600-800°C; And / or, the heat treatment time is 6-12h; and / or, cooling under an inert atmosphere after the heat treatment; And / or, the process of loading the nickel metal complex on the solid powder is: in an inert atmosphere, the solid powder is mixed with the second solvent and the nickel metal complex, stirred and the second solvent is evaporated to obtain the catalyst.
6. The preparation method according to claim 5, characterized in that: The inert atmosphere is a nitrogen atmosphere; and / or, the treatment temperature of the stirring treatment is 35-60° C. and the treatment time is 2-10 h; and / or, the evaporation temperature is 60-95°C; And / or, the second solvent includes one or more of n-hexane, n-heptane, cyclohexane, n-pentane, methylcyclopentane, and methylcyclohexane.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The preparation method of the nickel metal complex comprises: Acetyl α-diimine ligand of the structure shown in formula 3 is obtained, and the acenaphthenyl α-diimine ligand is mixed with a nickel source containing nickel dibromide to obtain a nickel metal complex shown in formula 2; the preparation process of the acenaphthenyl α-diimine ligand shown in formula 3 is: the compounds shown in formula 4 and formula 5 are subjected to a synthetic reaction to obtain the acenaphthenyl α-diimine ligand shown in formula 3; Formula 3: Formula 4: Formula 5:
8. The preparation method according to claim 7, characterized in that: The solvent used in the synthesis reaction of the compounds represented by Formula 4 and Formula 5 is C 1-4 Alcohol, preferably including one or both of anhydrous methanol and anhydrous ethanol; And / or, the solvent used in the step of mixing the acenaphthenyl α-diimine ligand with the nickel source containing nickel dibromide is one or more of tetrahydrofuran, anhydrous ether, pentane, cyclopentane, n-hexane, cyclohexane, heptane, methylcyclohexane, toluene, xylene, chlorobenzene, o-dichlorobenzene, o-xylene, and dichloromethane.
9. Application of silica gel supported nickel-vanadium bimetallic catalyst in ethylene polymerization.
10. The use according to claim 9, characterized in that: Alkyl aluminum is also added to the ethylene polymerization reaction, and the molar ratio of the alkyl aluminum to the nickel in the silica gel-supported nickel-vanadium bimetallic catalyst is 5-200:1; preferably, the molar ratio of the alkyl aluminum to the nickel in the silica gel-supported nickel-vanadium bimetallic catalyst is 10-100:1, and / or the alkyl aluminum is one or more of trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, diethyl aluminum monochloride, trioctylaluminum, methylaluminoxane, modified methylaluminoxane, and ethylaluminoxane; And / or, the process of ethylene polymerization reaction is: ethylene is mixed with a third solvent, a comonomer, and an alkyl aluminum, and then a silica gel-supported nickel-vanadium bimetallic catalyst is added to carry out polymerization reaction; preferably, ethylene and / or the third solvent are first dehydrated and deoxygenated before being mixed with the comonomer, and / or, the polymerization reaction conditions are 60-150°C, 0.5-8MPa, 10-240min, and / or, the third solvent includes one or more of n-hexane, n-heptane, methylcyclohexane, toluene or cyclohexane, and / or, the comonomer includes one or more of 1-butene, 1-hexene or 1-octene.
Citation Information
Patent Citations
Silica gel-supported alpha-diimine nickel olefine polymerization catalyst, preparation method and application
CN101619111A
Fluorine-containing alpha-diimine nickel coordination compounds for preparing polyolefin elastomer, intermediate, preparation method and application thereof
CN111303215A
Silica gel loaded zirconium-vanadium bimetallic complex as well as preparation method and application thereof
CN111848840A
Acenaphthyl alpha-diimine nickel complex, catalyst and application of acenaphthyl alpha-diimine nickel complex
CN116462715A
Amino-containing asymmetric acenaphthenyl alpha-diimine nickel complex as well as preparation method and application thereof
CN117820383A